"PENOPLEX" THERMAL INSULATION PLATES AND THEIR AREAS OF APPLICATION - Abdullayev Ikromjon Aminjanovich; Akbarov Jakhongir Nematjon ugli; Nomanov Mashrabjan Bohodirjan ugli (Journals Park Publishing, 2024)
Penoplex" thermal insulation plates are made by extrusion of polystyrene. The process of extrusion of polystyrene makes it possible to create a foamed material with a homogeneous structure composed of closed pores with a size of 0.1-0.2 mm. This article provides information about "Penoplex" thermal insulation boards and their areas of application.
Keywords: polystyrene, thermal insulation, foundation, construction, deformation, roof.